2002
DOI: 10.1046/j.1423-0410.2002.drfgv158.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of platelets in additive solutions: a pilot in vitro study of the effects of potassium and magnesium

Abstract: Storing platelets in an additive solution containing magnesium and potassium improves the functionality of the platelets, as measured by in vitro testing, and may allow a reduction of the amount of plasma required to be carried over to the final unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
86
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 16 publications
15
86
3
Order By: Relevance
“…25 Other studies have also shown the benefits of potassium and magnesium, and their combined effect results in better storage characteristics and less PLT activation. 11,14,15 These hypotheses need further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Other studies have also shown the benefits of potassium and magnesium, and their combined effect results in better storage characteristics and less PLT activation. 11,14,15 These hypotheses need further study.…”
Section: Discussionmentioning
confidence: 99%
“…These ASs are all based on presence of acetate, citrate, and saline, but may contain other ingredients, such as potassium and magnesium, phosphate, and glycerol. 3,[11][12][13][14][15] Prolonged storage of PLTs in AS is gaining more interest, as routine bacterial screening was introduced and pathogen inactivation of PCs became available. In the Netherlands and Belgium, bacterial screening of all produced PCs has been mandatory since 2001, 16 which enables the extension of the storage time of PCs beyond 5 days.…”
mentioning
confidence: 99%
“…PAS‐III adds phosphate to PAS‐II; it has been used in studies of pooled BC‐PCs, which undergo photochemical treatment for pathogen inactivation 31,32 . Magnesium and potassium have been added to PAS‐III, modified PAS‐III, or PAS IIIM 33 . Composol (Fresenius HemoCare, Emmer‐Compascuum, the Netherlands) is PlaymaLyte A with added citrate to prevent PLT clumping at very low plasma concentrations 34 .…”
Section: Origin Of the Buffy‐coat Methodsmentioning
confidence: 99%
“…Lower metabolic activity during storage is associated with expression of activation markers such as P‐selectin (CD62) at the PLT surface, 7,9 which suggests that PLTs gradually become activated during storage. The fact that storing of PLTs compromises functionality may also appear from the reduced hypotonic shock response, which determines resistance of PLTs to hypotonic conditions and is probably linked to the metabolic state 10 . These activation measurements though have limitations.…”
mentioning
confidence: 99%